Ready Player Two : Women Gamers and Designed Identity - Chess, Shira (Book collections on Project MUSE., 2017)
"Cultural stereotypes to the contrary, approximately half of all video-game players are now women. A subculture once dominated by men, video games have become a form of entertainment composed of gender binaries. Supported by games such as Diner Dash, Mystery Case Files, Wii Fit, and Kim Kardashian: Hollywood -- specifically marketed to women -- the video game industry is now a major part of imagining what femininity should look like. In Ready Player Two, media critic Shira Chess uses the concept of "Player Two"--The industry idealization of the female gamer -- to examine assumptions implicit in video games designed for women and their impact on gaming culture and the larger society. With Player Two, the video game industry has designed specifically for the feminine ideal: white, middle class, heterosexual, cisgendered, and abled. Drawing on categories from time management and caregiving to social networking, consumptions, and bodies, Chess examines how games have been engineered to shape normative ideas about women and leisure"--